PENGARUH INFLASI, RETURN ON ASSETS, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM - Adikerta, I Made Angga; Abundanti, Nyoman (E-Jurnal Manajemen, 2020)
The stock price is important for the company because it reflects the value of the company. Stock prices can change because of the influence of various factors, including: inflation, Return on Assets (ROA) and Debt to Equity Ratio (DER). This study aims to determine the effect of inflation, ROA, and DER on stock prices. This research was conducted on companies listed in the LQ-45 index on the Indonesia Stock Exchange during 2016-2018. The number of samples used in this study amounted to 34 companies with a purposive sampling method. The analysis technique used is multiple linear regression. The results of the analysis in this study indicate that inflation has no effect on stock prices, ROA has a positive effect on stock prices, and DER has a positive effect on stock prices. Keywords : Stock Prices, Inflation, Return on Assets, Debt to Equity Ratio.